2008
DOI: 10.1095/biolreprod.107.063370
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Promotes Luteal Cell Death in Bovine Corpus Luteum1

Abstract: Low oxygen caused by a decreasing blood supply is known to induce various responses of cells, including apoptosis. The present study was conducted to examine whether low-oxygen conditions (hypoxia) induce luteal cell apoptosis in cattle. Bovine midluteal cells incubated under hypoxia (3% O(2)) showed significantly more cell death than did those incubated under normoxia (20% O(2)) at 24 and 48 h of culture, and had significantly lower progesterone (P4) levels starting at 8 h. Characteristic features of apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 42 publications
2
47
3
2
Order By: Relevance
“…Each protein in the cultured bovine oviductal cells was detected by western blotting analysis as described previously (Nishimura et al 2008). Briefly, the cultured cells were lysed in 200 ml lysis buffer, and the protein concentrations were determined by the BCA method (Osnes et al 1993).…”
Section: Western Blottingmentioning
confidence: 99%
“…Each protein in the cultured bovine oviductal cells was detected by western blotting analysis as described previously (Nishimura et al 2008). Briefly, the cultured cells were lysed in 200 ml lysis buffer, and the protein concentrations were determined by the BCA method (Osnes et al 1993).…”
Section: Western Blottingmentioning
confidence: 99%
“…The response to hypoxia is important pathologically in the ischemic tissues, and is important physiologically in the process of embryo development in organ formation Wenger 2002;Bruick 2003;Wiesener and Maxwell 2003;Lee et al 2004; 11 Hellwig-Burgel et al 2005;Chen et al 2009;Dunwoodie 2009). We have previously suggested that hypoxia plays roles in both life (luteal formation) (Nishimura and Okuda 2010) and death (luteal regression) (Nishimura et al 2008) of CL. In the formation of CL, hypoxia induces angiogenesis (Nishimura and Okuda 2010), whereas it decreases P4 synthesis (Nishimura et al 2006) and promotes apoptosis during regression of the CL (Nishimura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously suggested that hypoxia plays roles in both life (luteal formation) (Nishimura and Okuda 2010) and death (luteal regression) (Nishimura et al 2008) of CL. In the formation of CL, hypoxia induces angiogenesis (Nishimura and Okuda 2010), whereas it decreases P4 synthesis (Nishimura et al 2006) and promotes apoptosis during regression of the CL (Nishimura et al 2008). These ideas are summarized in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations